2022
DOI: 10.1186/s13018-022-02983-z
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral-spreader-assisted anterior cervical discectomy and fusion prevents postoperative axial pain by alleviating facet joint pressure

Abstract: Objective To evaluate the relationship of postoperative cervical axial pain with different vertebral distraction methods used during ACDF procedures in cervical spondylosis patients. Methods Ninety-four single-level cervical spondylotic myelopathy patients with significantly loss of intervertebral disc height who underwent ACDF surgery in our institute between January 2018 and January 2020 were enrolled. Cervical spine lateral radiographs were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The cervical facet joint capsule is rich in receptors that can sense the intensity of physiological stimulation, and can produce a painful sensation when overstretched 19 . It is reported that uneven distraction of the facet joint is more likely to cause axial pain than an evenly over‐distracted facet joint 5 . Thus, we believe that a poor lordosis with axial distraction using zero‐profile implants may cause uneven joint distraction during the early months after the surgery, which may cause severe postoperative axial pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cervical facet joint capsule is rich in receptors that can sense the intensity of physiological stimulation, and can produce a painful sensation when overstretched 19 . It is reported that uneven distraction of the facet joint is more likely to cause axial pain than an evenly over‐distracted facet joint 5 . Thus, we believe that a poor lordosis with axial distraction using zero‐profile implants may cause uneven joint distraction during the early months after the surgery, which may cause severe postoperative axial pain.…”
Section: Discussionmentioning
confidence: 99%
“…The zero‐profile (Zero‐P) integrated interbody system can reduce the risk of instrument failure and postoperative dysphagia compared to traditional plate and cage system, which significantly increased the clinical outcome of ACDF treated CSM patients 4 . However, recent studies showed that postoperative axial pain is still a prominent complication that plagues many treated patients 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of axial symptoms can be up to 29.91% after ACDF ( Zhou et al, 2018 ) and 19.25% after laminoplasty ( Chen et al, 2021 ). Postoperative neck pain alleviation may be related to the transient relief of facet joint pressure during the vertebral distraction procedure in ACDF ( Xu et al, 2022 ). In the present study, cervical kyphotic correction causes significant improvement of axial symptoms postoperatively than preoperatively.…”
Section: Discussionmentioning
confidence: 99%